2016
DOI: 10.4236/ojg.2016.612109
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Sedimentary Environment and Sequence Stratigraphy of Middle-Late Permian Sediments in Coastal Fars, Iran (Zireh Gas Field, Well ZH-A)

Abstract: The current paper is focused on the facies, sedimentary environment and depositional cycles study of the Middle-Late Permian sediments in the South Fars Zireh Gas Field, the subsurface section of well ZH-A. Four hundred thin-sections obtained from cores and cuttings were examined under standard petrographic microscope. For this study research, Corel Draw X6, Corel Photo-Paint, DN2 Microscopy Image Processing System, Scope Photo, Autodesk Map, Geocalc and Auto Cad 2014 were utilized. Based on microfacies analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…It is suggested that Middle Permian carbonates of the region were deposited in a shallow marine environment. Correspondingly, similar shallow marine sediments, comprised mainly of subtidal facies were deposited during the middle-late Permian time in the Taurides and Iran (Altıner et al, 2000;Altıner & Özgül, 2001;Altıner & Şahin, 2012;Mehdipour Ghazi & Moazzen, 2015;Rezavand, Jahani, & Asilian, 2016;Şengör, 1990).…”
Section: Paleogeographic Implicationsmentioning
confidence: 95%
“…It is suggested that Middle Permian carbonates of the region were deposited in a shallow marine environment. Correspondingly, similar shallow marine sediments, comprised mainly of subtidal facies were deposited during the middle-late Permian time in the Taurides and Iran (Altıner et al, 2000;Altıner & Özgül, 2001;Altıner & Şahin, 2012;Mehdipour Ghazi & Moazzen, 2015;Rezavand, Jahani, & Asilian, 2016;Şengör, 1990).…”
Section: Paleogeographic Implicationsmentioning
confidence: 95%